Removal Escherichia Coli From Sewage Using Combination Of Electrocoagulation And Ultrasonic Method - Ibrahim, Nur Asyraf (Universiti Sains Malaysia, 2021)
Sewage is a combination of organic and inorganic effluent from diverse domestic, public, and industrial sources. Sewage also contains microorganisms that can cause sicknesses, such as protozoa and bacteria. Furthermore, sewage generates high contaminated and dirty wastewater. So, the sewage needs to be treated first before discharge to any river to avoid it polluted by this wastewater. The main objective of this study is to find the most efficient method that can treat the Escherichia coli in the sewage with different methods of treatment: electrocoagulation, sono-electrocoagulation and ultrasonic method. In this study, aluminium and iron electrodes were employed during the treatment procedure on anode and cathode electrodes, respectively. The aluminium and iron electrode were chosen as the electrode for this investigation because it was inexpensive and easy to obtain. The tests used in this study had various treatment times of 5 minutes, 10 minutes, 15 minutes, 20 minutes and 25 minutes, and varied voltages of 5V, 10V, 15V, 20V and 25V. Also, variable electrode distance which are1m, 2cm and 3cm. The highest percentage of E. coli removal is at the voltage of 25V, time treatment at 25min and electrode distance 1cm, which is 99.58% for electrocoagulation. For sono-electrocoagulation, the highest percentage of E. coli removal is at the voltage of 5V, time treatment at 25min and electrode distance 3cm, 99.31%. For ultrasonic method is 90.63% when the treatment time is 10min. Therefore, the most effective method to treat E. coli in sewage water is the electrocoagulation method. Then, followed by sono-electrocoagulation and ultrasonic.